Artem Oppermann
1 min readDec 26, 2018

--

Hey Aleksa. No it is correct as it is. As you can see the first part of the equations is just Eq. 5, which is: p(s=X, y=B)=N(s=X, y=B)/N. The second part is only multiplication by [n(s=X, y=B) + n(s=X, y= O)] in the denominator and numerator.

By doing so we get p(y=B|s=X)=N(s=X, y=B)/ [n(s=X, y=B) + n(s=X, y= O)] and p(s=X)=[n(s=X, y=B) + n(s=X, y= O)]/N which yields p(s=X, y=B)= p(y=B|s=X)*p(s=X)

--

--

Artem Oppermann
Artem Oppermann

No responses yet